2022
DOI: 10.1039/d1cc07164e
|View full text |Cite
|
Sign up to set email alerts
|

The importance, status, and perspectives of hybrid lanthanide-doped upconversion nanothermometers for theranostics

Abstract: Theranostics combines diagnostics and therapy in a single multifunctional system. Multifunctional upconversion luminescent lanthanide-doped nanothermometers for theranostic purposes offer non-invasive and sensitive multimodal performance in the biomedical field over traditional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…49 This work therefore once again highlights possibilities of employing various hybrid and inorganic (nano)materials for biomedical thermometry purposes as well as the potential of simultaneously coupling thermometry with another modality for theranostic purposes as has already been shown for other similar materials in literature. [50][51][52][53]…”
Section: Resultsmentioning
confidence: 99%
“…49 This work therefore once again highlights possibilities of employing various hybrid and inorganic (nano)materials for biomedical thermometry purposes as well as the potential of simultaneously coupling thermometry with another modality for theranostic purposes as has already been shown for other similar materials in literature. [50][51][52][53]…”
Section: Resultsmentioning
confidence: 99%
“…Most semiconductor QDs exhibit temperature-dependent spectral shifts and lifetime variations because of their bandgap changes with temperature . UCNPs with specific thermally coupled energy-level pairs, such as Er 3+ ( 2 H 11/2 and 4 S 3/2 ), Nd 3+ ( 4 F 5/2 and 4 F 3/2 ), and Eu 3+ ( 5 D 1 and 5 D 0 ), are commonly used for temperature sensing by monitoring the intensity ratio between the two related fluorescence bands, also known as ratiometric optical nanothermometry. , Fluorescent nanodiamonds for temperature sensing rely on the spin resonances of the nitrogen-vacancy center and their temperature-dependent shifts in the ODMR spectrum at microwave frequencies. − An important figure of merit for the comparison of nanothermometers is the relative thermal sensitivity, which is defined as the rate of change in the temperature-sensitive parameter with temperature, S normalr = | 1 Q ∂ Q ∂ T | , where Q denotes the temperature-sensitive parameter (intensity, lifetime, ratio) and T denotes temperature. S r is comparable between different systems with the consistent unit of K –1 or % K –1 .…”
Section: Probing Of Photothermal Heat Generationmentioning
confidence: 99%
“…The trivalent Eu ion is an excellent candidate for nanothermometer materials as it has a special electronic structure, and its fluorescence intensity is sensitive to temperature change. [17][18][19] Studies have shown that using longer wavelength photons for imaging could achieve deeper penetration, higher resolution, higher sensitivity, and better signal-to-noise ratios by reducing photon scattering and tissue autofluorescence for in vivo imaging in vivo. [20][21][22] However, poor biocompatibility, poor water solubility, and easy interference from the environment have limited the use of trivalent Eu ion-based probes for cellular analysis.…”
Section: Introductionmentioning
confidence: 99%